Androgen Receptor Expression in Breast Cancer: What Differences Between Primary Tumor and Metastases? - Giuseppe Bronte; Sara Bravaccini; Sara Ravaioli; Maurizio Puccetti; Emanuela Scarpi; Daniele Andreis; Maria Maddalena Tumedei; Samanta Sarti; Lorenzo Cecconetto; Elisabetta Pietri; Valeria De Simone; Roberta Maltoni; et al. (Translational Oncology, 2018)
Genomic studies have shown that the androgen receptor (AR) pathway plays an important role in some breast cancer subtypes. However few data are present on the concordance between AR expression in primary tumors and metastases. We investigated AR expression by using immunohistochemistry (IHC) in 164 primary tumors and 83 metastases, to explore its distribution in the different tumor subtypes and its concordance between the two sample types and according to sampling time. AR was more highly expressed in luminal A and B than HER2-positive and triple negative primary tumors. A similar distribution was found in metastases, and the concordance of AR expression between primary tumors and metastases was greater than 60%. No association between sampling time and AR expression was observed. We found a good concordance of AR expression between primary tumor and metastasis, but the variability remains high between the two types of specimens, regardless of the variation in sampling time. For this reason, if used for treatment decisions, AR evaluation should be repeated in each patient whenever a new biopsy is performed, as commonly done for the other breast cancer biomarkers.